Effects on growth performance, hematology, immune responses, intestinal histomorphology, carcass traits and meat quality in growing pigs of supplementing their diet with the yeast-rich residue from industrial production of ethanol from molasses - Pitukpol Pornanek (2020)
© 2020 Fundacion CIPAV. All rights reserved. Sixteen Landrace × Large White pigs (8 castrated males and 8 females) of 52.9±4.62 kg live weight were fed in individual pens for 38 days on basal diets of broken rice-soybean meal supplemented with four levels (0, 5, 10 and 15% as DM) of molasses-yeast-powder (MYP) (the dried, yeast-rich residue from ethanol production by fermentation-distillation of molasses). The MYP contained (DM basis) 37% protein, 14.7% β-glucan and 31% mannan-oligosaccharides. The design was a randomized block of four treatments each with four replicates. Blood samples were collected on the last day of the trial and evaluated for hematological and immunological parameters. Carcass characteristics, intestinal histomorphology and meat quality were measured postmortem. Growth rate and feed conversion were improved by 12 and 9%, respectively when 5% of MYP was added to the diets. For both traits, the dose-response curves were curvilinear, showing no further improvements in live weight gain and feed conversion beyond the 5% level of addition of the MYP. Supplementation with MYP appeared to have no effect on the hematology, intestinal histomorphology, immunological response, carcass traits and meat quality of the pigs.